How did antibiotic growth promoters increase growth and feed efficiency in poultry? - Fernandez Miyakawa, Mariano Enrique; Casanova, Natalia Alejandra; Kogut, Michael H. (Elsevier, 2024)
It has been hypothesized that reducing the bioenergetic costs of gut inflammation as an explanation for the effect of antibiotic growth promoters (AGPs) on animal efficiency, framing some observations but not explaining the increase in growth rate or the prevention of infectious diseases. The host's ability to adapt to alterations in environmental conditions and to maintain health involves managing all physiological interactions that regulate homeostasis. Thus, metabolic pathways are vital in regulating physiological health as the energetic demands of the host guides most biological functions. Mitochondria are not only the metabolic heart of the cell because of their role in energy metabolism and oxidative phosphorylation, but also a central hub of signal transduction pathways that receive messages about the health and nutritional states of cells and tissues. In response, mitochondria direct cellular and tissue physiological alterations throughout the host. The endosymbiotic theory suggests that mitochondria evolved from prokaryotes, emphasizing the idea that these organelles can be affected by some antibiotics. Indeed, therapeutic levels of several antibiotics can be toxic to mitochondria, but subtherapeutic levels may improve mitochondrial function and defense mechanisms by inducing an adaptive response of the cell, resulting in mitokine production which coordinates an array of adaptive responses of the host to the stressor(s). This adaptive stress response is also observed in several bacteria species, suggesting that this protective mechanism has been preserved during evolution. Concordantly, gut microbiome modulation by subinhibitory concentration of AGPs could be the result of direct stimulation rather than inhibition of determined microbial species. In eukaryotes, these adaptive responses of the mitochondria to internal and external environmental conditions, can promote growth rate of the organism as an evolutionary strategy to overcome potential negative conditions. We hypothesize that direct and indirect subtherapeutic AGP regulation of mitochondria functional output can regulate homeostatic control mechanisms in a manner similar to those involved with disease tolerance.